(untitled) (International journal of artificial intelligence, 2024)
Drying is one of the most ancient and widely used methods for preserving fruits and vegetables. The process reduces water activity, which inhibits microbial growth and enzymatic activity, ensuring extended shelf life. However, optimizing the drying process is crucial to preserve the nutritional value, color, texture, and flavor of the products while minimizing energy consumption and operational costs. . It is known that the drying process is one of the main links in reducing the costs of long-term storage and transportation of fruits and vegetables grown in agriculture. Accordingly, a systematic analysis of the process of drying fruits and vegetables was carried out in the research work, and the laws of interphase exchange in the capillary pore structure of the product during the heat-metabolism process, humidity and temperature changes in the layers of the product were studied. Based on research, a 6-level hierarchical structure was developed taking into account the generality of chemical, physic-chemical, biophysical, and metabolic processes This article delves into the principles of drying, factors affecting its efficiency, techniques for optimization, and advances in drying technologies for fruits and vegetables. The drying of fruit and vegetable products is a crucial process for preserving nutritional value, extending shelf life, and enhancing marketability.